CATHETER-BASED RENAL DENERVATION – LONG TERM SAFETY AND BLOOD PRESSURE REDUCTION IN PATIENTS WITH RESISTANT HYPERTENSION. (June 2022) - Schlaich, Markus; Sesa-Ashton, Jonathon; Lee, Rebecca; Lambert, Elisabeth; Lambert, Gavin; Nolde, Janis; Walton, Antony; Esler, Murray
Abstract : Objective: Recent sham-controlled andomised clinical trials have confirmed the safety and efficacy of catheter-based renal denervation (RDN) with clinically meaningful blood pressure (BP) reductions in hypertensive patients on or off antihypertensive medication. Longer-term safety and efficacy data have so far only been documented out to 3 years. Here we provide a first report on safety and efficacy outcomes in a cohort of patients with resistant hypertension beyond 5 years of follow up. Design and method: We recruited patients with resistant hypertension who were previously enrolled in various RDN trials applying radiofrequency energy to ablate the renal nerves using the Symplicity Flex® system. All participants had baseline assessments prior to RDN and repeat assessment at current long term follow up including medical history, automated office and ambulatory BP measurement, and routine blood and urine tests. Results: A total of 60 participants (age: 70.0 ± 10.3 years (mean ± SD), 76.3% male) have completed long-term follow up investigations with an average of 6.8 (range 6–10) years post-procedure. Ambulatory systolic BP was reduced by 12.0 ± 21.6mmHg (from 145.7mmHg to 132.8mmHg; p < 0.001) and diastolic BP by 8.3 ± 12.8mmHg (from 81.6 mmHg to 72.0 mmHg; p < 0.001). This BP reduction occurred despite participants being on less antihypertensive medication with a reduction in the average defined daily dose, the assumed average maintenance dose per day for a drug used for its main indication in adults, from 4.91 ± 0.37 to 4.02 ± 0.27 (p < 0.01). eGFR remained stable at long-term follow up with no statistically significant difference in participants with pre-existing CKD from baseline. Conclusions: Our investigation indicates a significant and robust reduction in ambulatory systolic and diastolic blood pressure, despite reduction in antihypertensive medications, in the long-term following catheter-based renal denervation without evidence of adverse consequences on renal function.